The U.P. President's end-of-term report, 1993-1999. ([University of the Philippines], 1999)
"Under the direction of the UP President, this 9 volume UP President's End-of-Term Report, covering the period 6 August 1993 to 5 August 1999, was prepared by the Office of the Vice President for Public Affairs in collaboration with the UP System Information Office; the Offices of the Vice Presidents for Academic Affairs, Finance and Administration, Planning and Development, and Information and Communication Systems; the Office of the Secretary of the University and the Office of Legal Services; the Offices of the Chancellors of all the UP autonomous universities; the Directors of the various System Offices, Centers, and Programs; and the Chairs of various Systemwide Committees for special programs and projects.